Comparison Between Intra-Articular Steroid Injection And Ultrasound Therapy in Management of Chronic Knee Osteoarthritis - Rashid, Maimuna; Iqbal, Waseem; Butt, Amir Waheed; Jamshed, Omer; Noor, Musab Bin; Mehdi, Syed Aoun Abbasi (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the mean pain score and range of motion in chronic knee osteoarthritis patients treated with intraarticular Steroid injection versus ultrasound therapy. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Rehabilitation Medicine, Combined Military Hospital, Pano Aqil Pakistan, from Oct 2020 to Apr 2021. Methodology: Patients were divided into two groups (50 patients in each group). One group received ultrasound therapy for six weeks, with three sessions per week. The second group received a single 80mg intraarticular Triamcinolone Acetonide. Patients in both the groups were monitored for six weeks to assess the pain score and range of motion. Results: A total of one hundred (100) patients with knee pain due to chronic osteoarthritis were included in the study. The mean age in the ultrasound group was 54 ± 4.8 years and in the intra-articular group, the mean age was 54 ± 4.7 years. The mean reduction in pain score and mean improvement in the range of motion were compared between two groups and statistically significant difference was observed (p-value <0.001). Conclusion: According to our findings, intra-articular Corticosteroid injection is more effective in comparison to ultrasound therapy. However, there were statistically significant reductions in pain scores and improvements in the range of motion in both groups.